(untitled) (Proceedings of Southern Federal University. Philology, 2018)
Yulia M. Sergeeva (Moscow, Russian Federation) The article raises one of the most controversial issues of linguistic semantics – the correlation of two or more meanings within a lingual sign. A necessary step to understand the meaning is interpretation – conscious analytical work of a person directed onto specification and individualization of the general sense. Empirical studies prove that ambiguity, i.e. the possibility to interpret one utterance in several ways, leads to misinterpretation of the sense and as such requires immediate clarification or else the communication might be defective. In order to systematize typical ambiguous utterances three basic types of ambiguity are introduced: syntactic, lexical and semantic, each one guarded by its own linguistic mechanism. It is argued that ambiguity can be intentional (equivocation, doublespeak) or unintentional (occasional language error or vagueness of expression). The latter is treated as pragmatic ambiguity (aka indeterminacy). Pragmatic ambiguity is caused by the fact that an utterance may have more than one meaning in the context in which it is uttered. The article is concluded with the statement that diversity of meanings result from the uniqueness of concepts as products of individual thinking. The presented material contributes to detection of problematic passages in a text, since it not only marks dubious sentences, but also explains the sources of their potential ambiguity. Key words: dialogue, addressee, implicature, ambiguity, interpretation, meaning, contextual situation. DOI 10.23683/1995-0640-2018-1-79-87